Interactive Effects of Silicon and Potassium Nitrate in Improving Salt Tolerance of Wheat - Bybordi Ahmad (Journal of Integrative Agriculture, 2014)
Adequate regulation of mineral nutrients might be effective to ameliorate the deleterious effects of salts and help to sustain crop productivity, particularly in glycophytes, under salt stress. In this study, laboratory and greenhouse experiments were carried out at Agricultural and Natural Resources Research Centre in East Azerbaijan, Iran, to investigate the interactive effects of silicon and potassium nitrate in alleviating NaCl induced injuries in wheat (Triticum aestivum L.). In the laboratory experiment, three winter wheat cultivars Pishgam, Afagh and Alvand were grown on sterile filter paper moistened with 20, 40, 60, 80, and 100 mmol L−1 NaCl solution. Results revealed that wheat cultivars were significantly different in their growth response to different concentrations of NaCl and Pishgam was found to be the most tolerant to NaCl stress, and used in the second part of study. In the greenhouse experiment, Pishgam was grown in a hydroponic system subjected to different NaCl levels (20, 60 and 100 mmol L−1) and treated by silicon (0, 2 and 4 mmol L−1, final concentration in nutrient solution using K2SiO3) and potassium nitrate (0, 0.5, 1, and 2 mmol L−1, foliar application). The experimental design was factorial based on a completely randomized design with three replications. It was found that NaCl stress significantly increased proline accumulation and sodium content in the plant tissues while decreased potassium uptake and accumulation by plants. Moreover, plant weight, 100-seed weight, relative water content, chlorophyll content, and photosynthesis were also significantly affected by varying levels of NaCl. However, exogenous application of silicon and potassium nitrate reduced sodium uptake, increased potassium and consequently improved plant weight, 100-seed weight, seed yield, ear length, and photosynthesis rate. This study suggested that utilization of the salt-tolerant cultivar (Pishgam) combined with proper foliar application of potassium nitrate (2 mmol L−1) and silicon (4 mmol L−1) at the wheat booting stage might be a promising approach to obtain higher grain yield on saline lands.